Metal‐Semiconductor Phase Transition in Multilayer VSe2 for Broadband Photodetector with High Sensitivity - Yujue Yang; Mengjia Xia; Qixiao Zhao; Zhidong Pan; Huafeng Dong; Xin Zhang; Fugen Wu; Juehan Yang; Nengjie Huo (Advanced Electronic Materials)
Abstract 2D 1T‐VSe2 is a charge‐density wave (CDW) system that also exhibits room‐temperature ferromagnetism, making it promising for photodetecting devices. However, the sensitivity of 1T‐VSe2 photodetectors is limited by the high dark current due to its metallic feature of T‐phase VSe2. So far, photodetectors based on semiconducting 2H‐phase VSe2 have ever been reported. In this work, the metal‐semiconductor phase transition (1T to 2H) in multilayer VSe2 by thermal annealing process, and the fabrication of 2H‐VSe2 broadband photodetectors with high sensitivity is reported. The 2H‐VSe2 photodetectors exhibit low dark current and a broad spectral range of 405–1550 nm. The responsivity (R) and detectivity (D*) can reach up to 75.26 A W−1 and 1.45 × 1010 Jones at Vsd of 1 V, outperforming photodetectors based on 1T‐VSe2 and other 2D materials for the 1550 nm optical communication band. This work showcases a facile method for obtaining the metal‐semiconductor phase transition of VSe2 and demonstrates the potential of 2H‐VSe2 for high‐performance near‐infrared photodetectors.